Drug survival of fumaric acid esters for psoriasis: a retrospective study. (6th August 2014) - Ismail, N.; Collins, P.; Rogers, S.; Kirby, B.; Lally, A.
Summary Background Fumaric acid esters (FAEs) have been used for over 30 years in the management of psoriasis. Objectives To determine drug survival of FAEs in patients with psoriasis, treatment‐limiting adverse drug events and the range of effective drug doses. Methods A retrospective, single‐centre study assessing all patients commenced on FAEs between October 2003 and July 2012. Demographic data, length of treatment, reasons for discontinuation of FAEs, side‐effects and range of doses were recorded. Results Two hundred and forty‐nine patients [160 (64%) male] were included. The mean age at which FAEs were commenced was 44·5 years (range 17–82 years). The mean length of treatment was 28 months (range 1 week to 106 months). In patients who were commenced on FAEs ≥ 4 years before inclusion in this study, the 4‐year drug survival was 60% (64/107). FAEs were discontinued in 146/249 patients (59%); this was due to lack of efficacy in 59/146 (40%) and gastrointestinal upset in 39/146 (27%). A very low dose of FAEs (< 240 mg daily) was successful in maintaining control of psoriasis in 26 (10%) patients. The mean treatment duration of these patients was 64 months (range 32–106 months). Conclusions Fumaric acid esters have a 4‐year drug survival rate of 60%, which compares favourably with reported 4‐year survival rates of 40% for etanercept and adalimumab and 70% for infliximab. Longer drug survival is more likely in the significant subgroup of patients in whom a very low dose of FAEs is sufficient to control disease. The reasons for this are unclear.